Enhanced nonlinear optical absorption in defect enriched graphene oxide and reduced graphene oxide using continuous wave laser z-scan technique. (2022) - Kumara, K.; Kindalkar, V.S.; Jyothi Serrao, Felcy; Chandra Shekhara Shetty, T; Patil, P.S.; Dharmaprakash, S.M.
Abstract: This work pertains to the investigation of the nonlinear optical (NLO) properties of defect enriched graphene oxide (GO) and reduced graphene oxide (rGO). The modified Hummers method approach was adopted to synthesize GO. The rGO was obtained by reducing GO using L-ascorbic acid. The X-ray diffraction patterns have confirmed the structure of GO and rGO. Optical phonons of the samples, excited by the visible laser light, are studied using Raman spectroscopy. After reduction, the optical band gap energy is decreased from 4.43 eV to 3.56 eV. The third-order NLO properties of defect enriched GO and rGO have been investigated by performing a single beam z-scan experiment. The nonlinear absorption coefficient of the samples is obtained from open aperture (OA) z-scan study by using a continuous-wave (CW) laser at 532 nm. Reverse saturable absorption behaviour is observed in both samples. The self-defocusing of the laser beam and negative nonlinear refractive index is determined from the closed aperture data. NLO behaviour is found to increase with the increase in defects/disorder. The optical limiting property of GO and rGO was investigated by using OA data and both samples have shown improved optical limiting values. Thus thr defect enriched GO and rGO may be strong contenders for optical limiting applications.